Comparatives Study of Soil Organic Carbon (SOC) under Forest, Cultivated and Barren Land: A Case of Chovar Village, Kathmandu - Bhandari, S; Bam, S (Nepal Journal of Science and Technology, 2014)
The study was carried out in Chovar village of Kritipur Municipality, Kathmandu to compare the soil organic carbon (SOC) of three main land use types namely forest, agricultural and barren land and to show how land use and management are among the most important determinants of SOC stock. Stratified random sampling method was used for collecting soil samples. Walkley and Black method was applied for measuring SOC. Land use and soil depth both affected SOC stock significantly. Forest soil had higher SOC stock (98 t ha-1) as compared to agricultural land with 36.6 t ha-1 and barren land with 83.6 t ha-1. Similarly, the SOC in terms of CO22-1, 79.27 to 22.02 CO2-e ha-1 and 121.11 to 80.74 CO2-1 for 0- 20 cm to 40-60 cm soil depth, respectively. Bulk density (BD) was found less in forest soil compared to other lands at all depths, which showed negative correlation with SOC. The study showed a dire need to increase current soil C stocks which can be achieved through improvements in land use and management practices, particularly through conservation and restoration of degraded forests and soils. DOI: http://dx.doi.org/10.3126/njst.v14i2.10422 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 103-108